(untitled) (Archive of Conferences, 2020)
Although the Uzbek and world literature, Roya or Gulistan, and the Law of Eternity are written in two different styles, the main idea is a common depiction of society’s relationship to man and man’s relationship to society. We can also see that in both works the main theme is expressed mainly by dream motifs. The article describes the evolution of the human personality through images, dialogues, symbols, and the image of the existing system on the basis of common ideas.